TRANSMISI NILAI DAN KEILMUAN KITAB KUNING DI ERA DIGITAL: (Studi Etnopedagogi pada Pesantren Tradisional dan Modern di Tapanuli) - Faisal Musa; Marwah (Pascasarjana Universitas Al-Qolam Malang, 2025)
This research examines the continuity and transformation of the Kitab Kuning teaching tradition in traditional and modern pesantren in the Southern Tapanuli region. This research uses a qualitative approach with field observation and in-depth interviews. The results show that traditional pesantren wtihin Musthafawiyah pesantren network still maintain the teaching of the Kitab Kuning with the sorogan and bandongan methods as the core of knowledge and value transmission. This reflects the practice of ethnopedagogy rooted in local culture is still quite strongly maintained. In contrast, modern pesantren, especially the Gontor network such as the Pesantren Modern Unggulan Terpadu Darul Mursyid and the Pesantren Modern Al Abraar adopt the integration model of the national curriculum and prioritize general knowledge, making the Kitab Kuning as a complement. Digital technology has also begun to be integrated as learning support, although direct kiai-santri interaction remains the main key. This finding shows the emergence of a hybrid learning model that aligns with Graham's Blended Learning and Mezirow's Transformative Learning concepts, which emphasize the existence and importance of effective integration between face-to-face learning and digital technology to increase the effectiveness of pedagogy. Thus, the process that occurs in pesantren in Tabagsel can be read as a form of transformation of Islamic education that is authentic and reflective of changing times.